The demand for crop genetic resources from international collections - Fowler, Cary; Smale, Melinda; Gaiji, Samy (International Food Policy Research Institute, 2003)
It is commonly known that most major agricultural crops were domesticated over a period of a thousand years in what are now termed “developing” countries of the “South.” Path-breaking conservationists such as Vavilov (1926) and Harlan (1975) have documented the great genetic diversity found in these countries. There is little doubt that the flow of crop genetic resources from developing countries to Europe and North America provided much of the biological foundation for agriculture in today’s developed countries (Fowler 1994).